Data Mining Dalam Perusahaan PT Indofood Lubuk Pakam - M. Risqi Ananda; Nurul Sandra Maharani; Eka Fadhila; Alvia Rahma; Nurbaiti Nurbaiti (CV. ITTC INDONESIA, 2023)
Indofood is engaged in the distribution of food and beverages, which faces business competition with several other companies. This study aims to identify patterns and trends in big business data, predict future behavior and trends, and provide insight into ongoing business performance using data mining. This article discusses the application of data mining at PT. Indofood to analyze sales data and see which sales are most in demand by consumers, especially sales of food and beverages. Qualitative and clustering methods are used in this study, and the application applied can assist companies in making decisions to improve product sales models. The benefit is that it makes big data analysis easier and provides insight into processed sales data. In this study, the results obtained in the form of applications that can assist companies in making decisions to create a better product sales model.